Oil Demand Shifts for The Period 2000-2018 And Its Future Trends - Nima Bekheet, Heider; Jawad Juma, Mohemmad (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research comes from identifying the changes in the structure of oil demand and the reasons behind these transformations and their impact on the stability of the oil market during the period 2000- 2018. What are the future trends in World Oil Demand, The research was based on the hypothesis that "any shift in the demand side of oil that contributes to high or lower demand rates will have reflections on the stability of the international oil market.”? The study revealed a set of conclusions, the most important of which was that there is a fundamental shift in the structure of oil demand, as the dynamics of oil demand shifted from industrialized countries represented by OECD to developing countries non-OECD mainly in emerging countries like China and India.